Study on multi-cycle reaction performance of Fe/Al compound oxygen carriers in chemical-looping pyrolysis of coal tar. (18th May 2020) - Wang, Cuiping; Gong, Jian; Cui, Weiwei; Wang, Fengyin; Bai, Hongcun; Hu, Xiude; Guo, Qingjie
Graphical abstract: Figure. Carbon black (CB) yields in the multi-cycle chemical looping pyrolysis process of coal tar with two oxygen carriers, one is Fe/Al compound oxygen carrier, and another is Fe/Al compound oxygen carrier modified by CaO. Highlights: The multi-cycle redox reactions of iron OC in coal tar pyrolysis are investigated. The mechanism of OC deactivation is synthetic action of carbon deposition and sintering. The iron OC modified by CaO improved the persistence of oxygen carrying capacity. Abstract: Two Fe/Al compound oxygen carriers were prepared by the impregnation method, in which one is CaO-modified, and they were applied in multi-cycle experiments of preparing carbon black (CB) by chemical-looping pyrolysis of coal tar in a small fluidized bed reactor in laboratory. X-ray diffraction, N2 adsorption analysis, and scanning electron microscopy were employed to analyze the variation of composition, the pore distribution, and the surface morphology of the OCs during the cyclic reaction. XRD results show that the oxygen-carrying capacity of both two-compound OCs decreases with the increase of the number of cycles, but the CaO-modified OC performs better for carbonation of CaO and then thermal decomposition of CaCO3 during the cycle reaction. BET and SEM results show that the Fe/Al compound OC can maintain a good porous structure during the first 15 cycles. As the cycle numbers continuously increase, the sintering accumulation appears on the OC surface, resulting in an increase in the tar volatiles' diffusion resistance on the surface of the particles. The CaO-modified compound OC maintained a good porous structure during 20 cycles. The decrease of the oxygen-carrying capacity and the surface sintering of the OC are the main reasons for the decrease of the reaction activity. The CaO carbonation-decomposition can maintain the porous structure of the compound OC during the multi-cycle reaction and delay the surface sintering effectively, thus improving the reaction performance of the OC.